A thematic and artistic comparison between the poems "Sunset Garden" and "Fever" by Ghazi Al-Gosaibi - Alshedookhi, Khalid Saleh (Journal of Arabic Language Sciences and Literature, 2025)
This study presents a thematic and artistic comparison between two poems "Garden of Sunset" and "Fever" by the Saudi poet Ghazi Al-Gosaibi, aiming to explore the similarities and differences between them, and to reveal the development of the poet’s experience and vision of life and the world. The poem "Garden of Sunset" represents the stage of intellectual and artistic maturity in Al-Gosaibi’s experience, as he wrote it in the late period of his life, expressing a balanced vision of life and death characterized by reconciliation and acceptance. Meanwhile, the poem "Fever" reflects the stage of crisis and struggle experienced by the Arab intellectual with his cultural and social reality, characterized by rejection, rebellion, and pessimism. The study concluded that the two poems differ in their contents, main ideas, poetic imagery, and linguistic styles. "Garden of Sunset" is distinguished by the multiplicity of its psychological, emotional, patriotic, and divine dimensions, with sincere emotion, simplicity and sweetness of vocabulary, and the blending of romance and elegy. As for "Fever," it is characterized by organic unity, dramatic paradox, melancholic poetic lexicon, deep symbolism, and pessimistic tendency. The relationship between the two poems reflects development and elevation in Al-Gosaibi’s poetic and human experience, from the stage of struggle and rejection to the stage of maturity and reconciliation. It can be said that Al-Gosaibi in "Garden of Sunset" was able to absorb his previous experience in "Fever" and transcend it, incorporating it into a more comprehensive and deeper vision of life and death that acknowledges pain and suffering but transcends them to reconciliation and acceptance.